2021
DOI: 10.1177/14777606211019414
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic pyrolysis of recycled HDPE, LDPE, and PP

Abstract: Plastic waste has been growing every year, and as a result, environmental concern has been a topic of much attention. Many properties of plastics, such as their lightweight, durability, and versatility, are significant factors in achieving sustainable development. The exponential increase of plastic production produces every year approximately 100 million tons of waste plastic, which could be converted into hydrocarbon fuels by employing a process appropriately called pyrolysis. Pyrolysis, which is thermal or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Common catalytic pyrolysis catalysts include various acidic zeolites (ZSM-5, HZSM-5, HY, USY, etc.) [39][40][41][42][43] and catalytic cracking (FCC) catalysts. 44 Both thermal and catalytic pyrolysis proceed together during the reaction process.…”
Section: Thermal and Catalytic Pyrolysismentioning
confidence: 99%
“…Common catalytic pyrolysis catalysts include various acidic zeolites (ZSM-5, HZSM-5, HY, USY, etc.) [39][40][41][42][43] and catalytic cracking (FCC) catalysts. 44 Both thermal and catalytic pyrolysis proceed together during the reaction process.…”
Section: Thermal and Catalytic Pyrolysismentioning
confidence: 99%
“…The vibration band located at 718–729 cm −1 corresponds to the swing in the plane of the connections in the methylene group 28 . The bending vibration and symmetry vibration of the CH 2 bonds in the main chain was associated with the signal at 1450–1480 cm −1 29,30 . The signal at 2846–2914 cm −1 was related to CH's symmetric and asymmetric stretching vibrations 31 .…”
Section: Resultsmentioning
confidence: 94%
“…Over the years, numerous catalysts have been developed for obtaining better gasoline selectivity and converting waste plastics to liquid fuel. Catalysts developed so far for the degradation of polyolefins are mostly based on zeolite HZSM-5 (Aguado et al, 1997;Lin et al, 2004;López et al, 2011;Sivagami et al, 2022), Zeolite-Y (Manos et al, 2001;Shoaib et al, 2021), silicaalumina (SiO 2 -Al 2 O 3 ) (Aguado et al, 1997;Uddin et al, 1997), mesoporousaluminosilicate (MCM-41) (Aguado et al, 1997;Lin et al, 2004), FCC catalysts and clays (Manos et al, 2001;Rahman et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The combination of ZSM-5/MCM-41 catalyst provided less gaseous product (91.45% gaseous product and 3.58% liquid) than only using ZSM-5 (Lin et al, 2004). Shoaib et al (2021) pyrolyzed HDPE and LDPE using zeolite Y and found that pyrolysis of both HDPE and LDPE provided 71% liquid at 450 C at a catalyst-toplastic ratio of 1:5. Manos et al (2001) used clay and ultrastable Y zeolite to crack HDPE and found that clay catalysts can provide higher amounts of liquid than Y zeolite.…”
Section: Introductionmentioning
confidence: 99%